Liberation of women: seeking light through Islam (women’s rights in marriage) - Ahmad, Nadzrah; Ghazali, Norzulaili; Ismail, Nurul Syuhada (2016)
Women’s rights issues had marked its spot as one of the most debated issues throughout centuries. Whenever the issue is raised, the topic of marriage is the most highlighted concerning the discussion. Marriage is regularly portrayed as an “oppressive sphere” for women, with their rights being oppressed the moment they enter a marriage contract, especially in Islam. However, further reflection on the issue has shown that Islamic matrimony liberates women, preserves their honour and place in society, and abolishes injustice, when guided in principle from al-Quran and the Sunnah of Prophet Muhammad (s.a.w). Regrettably, Muslim malpractice and cultural interpretation of original Islamic teachings have tainted the true Islamic ideal. In dealing with the data, the study utilises an inductive method and content analysis, and aims to draw attention to the misunderstandings of marriage in Islam in regards to women rights. Further discussion will serve to explore the outcome of women’s rights in marriage as bestowed by Islam, and understand the importance of the marriage institution, whilst examining the compelling misunderstandings by detractors.